MULTIMODAL IMAGING AND ELECTRORETINOGRAPHY IN LONG-CHAIN 3-HYDROXYACYL COENZYME A DEHYDROGENASE DEFICIENCY. (2017) - Lin, James; Boudreault, Katherine; Tsang, Stephen
Abstract : Purpose: To report a case of pigmentary retinopathy in long-chain 3-hydroxyacyl coenzyme A dehydrogenase deficiency using multimodal imaging techniques. Methods: Case report. Results: An 8-year-old boy with a history of failure to thrive and a diagnosis of long-chain 3-hydroxyacyl coenzyme A dehydrogenase deficiency was referred for examination. Examination revealed a pigmentary retinopathy with macular atrophy; electroretinography results were consistent with a rod–cone dystrophy. Fundus autofluorescence and optical coherence tomography revealed retinal pigment epithelium atrophy. Follow-up examination findings showed increased severity of retinopathy on electroretinography, with optical coherence tomography angiography revealing enhanced visualization of choroidal vessels. Conclusion: This report reveals that long-chain 3-hydroxyacyl coenzyme A dehydrogenase deficiency can be characterized as a progressive rod–cone dystrophy, with multi-modal imaging techniques used to describe this condition. In particular, optical coherence tomography angiography can be used to further characterize this condition. Abstract : The authors present a case of an 8-year-old boy with rod–cone dystrophy secondary to long-chain 3-hydroxyacyl coenzyme A dehydrogenase deficiency, characterized using electroretinography and imaging modalities such as optical coherence tomography angiography.